Clinical performance of pressable glass-ceramic veneers after 5, 10, 15, and 20 years: A retrospective case series study - ÖZKAN, YASEMİN; ASLAN, YILMAZ UMUT (WILEY, 2019)
Objectives To evaluate the long-term clinical performance and survival rate of pressable lithium-disilicate glass-ceramic veneers (LDSVs). Materials and Methods A total of 413 LDSVs were bonded to anterior and posterior teeth by three experienced clinicians between 1998 and 2012. The LDSVs were examined for color/ esthetic match of the glass-ceramic surface (esthetic evaluation), fracture rate, marginal discoloration (staining of the luting cement), and marginal integrity (including caries, clinical evaluation). For clinical and esthetic evaluations, the modified United States Public Health Services (USPHS) score was used in this study. The success rate was determined with a Kaplan-Meier survival analysis. Results The mean observation time was 11.33 +/- 4.85 years. There was no loss to follow-up, all restorations were accounted for in the final analysis. The probability of survival of the 413 veneers was 98% after 5 years, 95% at 10 years, 91% at 15, and 87% at 20 years, indicating a very low clinical failure rate. Of the 413 restorations, complications were occurred in 15 (3.63%) of all restorations, and fractures and debonding in 6 (1.45%) and 9 (2.18%), respectively. Conclusions The LDSVs showed high survival rate and very good results for color match and anatomic form and marginal integrity in the long-term analysis. Clinical Significance The long-term performance of LDSVs can be considered as highly favorable when carefully planned.
Keywords: clinical long-term study; esthetic restorations; glass-ceramics; lithium disilicate; veneers; PORCELAIN LAMINATE VENEERS; PREPARATION DESIGNS; SURVIVAL; RESTORATIONS; METAANALYSIS; FAILURE; PERIOD; RATES